2014
DOI: 10.1089/ars.2013.5702
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitochondrial Electron Transport Chain Activity at Complex I Is Regulated byN-Acetylcysteine in Lymphocytes of Patients with Systemic Lupus Erythematosus

Abstract: Aims: Systemic lupus erythematosus (SLE) patients' peripheral blood lymphocytes (PBL) show mitochondrial dysfunction and oxidative stress. To determine the electrochemical bases of mitochondrial dysfunction, we measured electron transport chain (ETC) activity and its regulation by N-acetylcysteine (NAC) that reversed glutathione depletion and improved disease activity in SLE. ETC activity was assessed in PBL of 69 SLE patients and 37 healthy donors. Negatively isolated T cells were examined in 7 SLE patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 30 publications
1
54
1
Order By: Relevance
“…Studies have indicated that NAC can decrease the oxygen consumption in mitochondria (21) and block mTOR, a regulator of oxygen consumption and oxidative stress in mitochondria (22), which is consistent with the present finding that NAC increased the GSH and decreased the 8-iso-PGF2α levels in LN. Accordingly, after 12 weeks of treatment, the relative indexes, such as WBC, 24-h urine protein and ESR, were largely improved, and the SLEDAI was notably decreased, reflecting a satisfactory therapeutic outcome.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have indicated that NAC can decrease the oxygen consumption in mitochondria (21) and block mTOR, a regulator of oxygen consumption and oxidative stress in mitochondria (22), which is consistent with the present finding that NAC increased the GSH and decreased the 8-iso-PGF2α levels in LN. Accordingly, after 12 weeks of treatment, the relative indexes, such as WBC, 24-h urine protein and ESR, were largely improved, and the SLEDAI was notably decreased, reflecting a satisfactory therapeutic outcome.…”
Section: Discussionsupporting
confidence: 93%
“…However, NAC treatment inhibited the activity of Complex I but not Complex IV. This could be because NAC acts as a redox sensor by inhibiting the Complex I activity and limiting the oxygen and NADH utilization, thus reducing oxidative stress [52]. Complex I may also be inhibited by excess GSH through glutathionylation [53] since NAC treatment results in an increase in GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…9 The decreased activity of Complex I in our study may be related to the reverse electron transfer (RET), which may influence the mitochondria to produce elevated levels of ROS. Doherty et al (2014) reported the elevated levels in the complex I activity in peripheral blood lymphocytes of SLE patients measured by the levels of oxygen consumption. 34 It is in contrast with our study, however, as we studied the activity of enzyme complexes themselves, from isolated mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Doherty et al (2014) reported the elevated levels in the complex I activity in peripheral blood lymphocytes of SLE patients measured by the levels of oxygen consumption. 34 It is in contrast with our study, however, as we studied the activity of enzyme complexes themselves, from isolated mitochondria. The population of cells we studied involved monocytes too, and it is this cell that is known to fight using its armory of ROS.…”
Section: Discussionmentioning
confidence: 99%